Corrigendum: Antifungal evaluation of turmeric rhizome extract against Colletotrichum capsici, the causal agent of anthracnose on red-chili peppers (Capsicum annuum L.) - Akin, Hasriadi Mat; Anggraini, Desma; Wibowo, Lestari; Prasetyo, Joko; Suharjo, Radix (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2024)
A corrigendum on Antifungal evaluation of turmeric rhizome extract against Colletotrichum capsici, the causal agent of anthracnose on red-chili peppers (Capsicum annuum L.) by Akin, HM, Aggraini D, Wibowo L, Prasetyo J & Suharjo R. 2024. J. Trop Plant Pests Dis. 24(1): 75–81. https://doi.org/10.23960/jhptt.12475-81 In the original article, on page 77, the formula for disease intensity has an incomplete legend.  The authors apologize for this mistake and clarify that it does not affect the scientific conclusions of the article. The original version has been corrected Read original article >